Ellen Glasgow - American Writers 33 : University of Minnesota Pamphlets on American Writers - Auchincloss, Louis (Book collections on Project MUSE., 1964)
Ellen Glasgow - American Writers 33 was first published in 1964. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.